Health care utilisation (Edition 2016) (OECD Health Statistics, 2016)
This dataset includes statistics comparing different countries' level of health care use in terms of prevention, immunisation, screening, diagnostics exams, consultations, in-patient utilisation, average length of stay, diagnostic categories, acute care, in-patient care, discharge rates, transplants, dialyses, ICD-9-CM. The data is comparable with respect to units of measures such as days, percentages, population, number per capita, procedures, and available beds